PENGARUH KESADARAN WAJIB PAJAK, PERSEPSI KEADILAN PAJAK, SANKSI PAJAK, DAN KEPERCAYAAN PADA PEMERINTAH TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI JAKARTA BARAT - Theodore , Diviana; Jonnardi, Jonnardi (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to know the influence of taxpayer awareness, perception of tax justice, tax sanction, and trust in government on taxpayer compliance of west Jakarta. Conveniece sampling method was chosen for this sample and the entire legitimate information turned into a hundred respondents. The processing strategies the usage of a descriptive statistical analysis what helped by using the SmartPls. The results of this research is perception of tax justice and tax sanction have an influence on taxpayer compliance. While taxpayer awareness and trust in government didn’t have any influence of taxpayer compliance. This implication can provide input and add insight related to taxation and is expected to be additional information regarding to the factors that have an impact on taxpayer compliance to help the government increase tax revenue.